(untitled) (Asian Journal of Applied Sciences, 2015)
Fertilizing must be considered in cultivation of oil palm especially the type and rate of a fertilizer. The use of the type and rate of a fertilizer should be acurate to support the growth and the production of oil palm. The objectives of this research were to study the pattern of the plant growth response and to determine the optimum rate of the N, P, and K single fertilizer package rate on two years old immature oil palm. This research was conducted from April 2014 to march 2015 at IPB-Cargill Teaching of Oil Palm, Jonggol, Bogor, West Java, Indonesia. The design was used randomized block design with one factor and three replications. The fertilizer treatment were four packages, they were: control (P0), fertilizer 1125 g urea + 975 g SP-36 + 1125 g KCl + 50 g borat + 50 g CuSO4.5H2O each plant (P1), fertilizer 2250 g urea + 1950 g SP-36 + 2250 g KCl + 50 g borat + 50 g CuSO4.5H2OÂ each plant (P2), fertilizer 4500 g urea + 3900 g SP-36 + 4500 g KCl + 50 g borat + 50 g CuSO4.5H2O each plant (P3). The result showed that the application of N, P, and K single fertilizer package linearly significant to plant height, stem girth, leaf number, andÂ frond length number nine but did not significant Â to leaf area of frond number nine and all of physiological variables. The optimum rate of N, P, and K single fertilizer package can not be set because the effect of fertilizer still linier.